MEASURING BUILDING INFORMATION MODELLING (BIM) COMPETENCIES AMONG ARCHITECTURAL PRACTITIONERS IN EDO STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Implementing Building Information Modeling (BIM) is an innovative and transformative strategy within the construction sector. Exploring competency in BIM is a fundamental building block of architectural capability in contemporary society. The present study measured Building Information Modelling (BIM) competencies among architectural practitioners in Edo State, Nigeria. The study adopted a cross-sectional survey design, and architectural practitioners (n=59) in Edo State responded to the research questionnaire. The results of the Likert-type scale administered to the respondents revealed that only 11% have low BIM competence. In comparison, 31% of respondents demonstrated moderate competence, and 54% demonstrated high competence in BIM. Thus, the data show positive results for BIM competence.